The Development of a Toolkit & Guidelines to Support Peer Engagement - Kelly, Peter; O'Neill, Debra (Trinty College Dublin- UISCE, 2024)
The report explores the importance of peer engagement in harm reduction and advocating for the active involvement of marginalized community members in decision-making processes. It emphasizes the need for moving beyond tokenism to meaningful engagement, where peers, particularly people who use drugs (PWUD) are given real power to influence policy and services. The findings from this report also inform the toolkit and guidelines which was co-produced by the peer network and the academic researchers in partnership.
PUBLISHED
Keywords: Inclusive Society; Addiction and substance abuse; Leadership in nursing; Public health; Mental Health/Psychosocial disability; Health; Policy